Importância de Yersinia enterocolitica em microbiologia médica - Falcão, Juliana Pfimer; Falcão, D. P. [UNESP] (My University, 2006)
Y. enterocolitica is a human invasive enteropathogen which causes a number of intestinal and extraintestinal clinical symptoms of various degrees of severity, ranging from mild gastroenteritis to mesenteric lymphadenitis, which mimics appendicitis and in rare cases can evolve to septicemia. Infection by Y. enterocolitica can also lead to post-infection immunological sequelae including arthritis, erythema nodosum and glomerulonephritis. Pathogenic Y. enterocolitica strains have traditionally been linked to specific biotypes and serogroups and associated to a variety of phenotypic characteristics related to virulence. Molecular genetics studies have pointed to the importance of the pYV virulence plasmid, which encodes various virulence genes, as well that of specific chromosomal virulence genes, in determining the pathogenesis of this bacterium. Intestinal infections by Y. enterocolitica are mostly self-limiting and usually do not need an antibiotic treatment. The occurrence of this microorganism is not as frequently described in Brazil as it is in other countries, such as Japan, USA and many European countries. This review focuses on the general characteristics, pathogenesis, clinical symptoms, virulence characteristics, treatment and antibiotic susceptibility of Yersinia enterocolitica strains isolated in Brazil and around the world.
Importance of Yersinia enterocolitica in medical microbiology
Keywords: Clinical symptoms; Pathogenesis; Treatment and antibiotic susceptibility; Virulence; Y. Enterocolitica; aminoglycoside; ampicillin; antibiotic agent; bacterial protein; carbenicillin; cefotaxime; ceftriaxone; cephalosporin; ciprofloxacin; cotrimoxazole; doxycycline; lipopolysaccharide; penicillin G; virulence factor; antibiotic resistance; antibiotic sensitivity; appendicitis; arthritis; bacterial gene; bacterial strain; bacterial virulence; blood group typing; clinical feature; erythema nodosum; gastroenteritis; geographic distribution; glomerulonephritis; human; mesenteric lymphadenitis; molecular genetics; nonhuman; pathogenesis; plasmid; review; septicemia; Yersinia enterocolitica; yersiniosis